(untitled) (Research, Society and Development, 2022)
Invented in the 19th century, electric cars were not competitive enough to compete with combustion cars during the 20th century. With the growth of sustainable thinking and the debate about pollution, the environment and climate change, the burning of fossil fuels and the pollution generated by the process have become hotspots in the ecological debate. Due to the urgency of climate change, greater investments were made in technologies that minimize the problem and companies with more ecological proposals appeared on the market. This work aimed to concatenate and compare the main conclusions available in the contemporary literature regarding the use of battery electric cars, in order to describe their environmental impacts, especially when compared to conventional cars. It was concluded that the switch to electric cars is environmentally positive when combined with the change in energy matrix to renewable sources, reaching a 34% reduction in greenhouse gas emissions in certain studies. However, it is noteworthy that there was great variability of results regarding the reductions in emissions of these gases, with similar studies reaching results that differed 4.5 times from each other, due to the assumptions used. Alternatives were also found to enhance this migration of transport technology, such as carbon taxation policies, and negative aspects of electric cars, such as ocean and soil acidification and high human toxicity compared to combustion cars.